Injury-Mediated Vascular Regeneration Requires Endothelial ER71/ETV2. Issue 1 (January 2016) - Park, Changwon; Lee, Tae-Jin; Bhang, Suk Ho; Liu, Fang; Nakamura, Rei; Oladipupo, Sunday S.; Pitha-Rowe, Ian; Capoccia, Benjamin; Choi, Hong Seo; Kim, Tae Min; Urao, Norifumi; Ushio-Fukai, Masuko; et al.
Abstract : Objective—: Comprehensive understanding of the mechanisms regulating angiogenesis might provide new strategies for angiogenic therapies for treating diverse physiological and pathological ischemic conditions. The E-twenty six (ETS) factor Ets variant 2 (ETV2; aka Ets-related protein 71) is essential for the formation of hematopoietic and vascular systems. Despite its indispensable function in vessel development, ETV2 role in adult angiogenesis has not yet been addressed. We have therefore investigated the role of ETV2 in vascular regeneration. Approach and Results—: We used endothelial Etv2 conditional knockout mice and ischemic injury models to assess the role of ETV2 in vascular regeneration. Although Etv2 expression was not detectable under steady-state conditions, its expression was readily observed in endothelial cells after injury. Mice lacking endothelial Etv2 displayed impaired neovascularization in response to eye injury, wounding, or hindlimb ischemic injury. Lentiviral Etv2 expression in ischemic hindlimbs led to improved recovery of blood perfusion with enhanced vessel formation. After injury, fetal liver kinase 1 ( Flk1 ), aka VEGFR2, expression and neovascularization were significantly upregulated by Etv2, whereas Flk1 expression and vascular endothelial growth factor response were significantly blunted in Etv2 -deficient endothelial cells. Conversely, enforced Etv2 expression enhanced vascular endothelial growth factor–mediated endothelial sprouting from embryoid bodies. Lentiviral Flk1 expression rescued angiogenesis defects in endothelial Etv2 conditional knockout mice after hindlimb ischemic injury. Furthermore, Etv2 +/− ; Flk1 +/− double heterozygous mice displayed a more severe hindlimb ischemic injury response compared with Etv2 +/ − or Flk1 +/ − heterozygous mice, revealing an epistatic interaction between ETV2 and FLK1 in vascular regeneration. Conclusions—: Our study demonstrates a novel obligatory role for the ETV2 in postnatal vascular repair and regeneration. Abstract : Supplemental Digital Content is available in the text.